The Relationship between Village Government and Community in Village Development in Mungguk Bantok, Indonesia - Adib, Muhammad Adib Alfarisi; Heriyanto (Program Studi Ilmu Pemerintahan, FISIP - Universitas Halu Oleo, 2024)
This article explores the relationship between the village government and the community in organizing community participation in a collaborative model in Mungguk Bantok Village, Sintang, Indonesia. This is a qualitative study that uses a normative-juridical approach. The results of this study found that the correlation between the Mungguk Bantok Village Government and the community that organizes participation is still not well systemized and patterned, so it requires more optimal collaboration between the village government and the community in developing the village so that village development can be achieved. The authors found efforts to develop the village with cooperative, participatory, emancipative, transparent, responsible, and sustainable development. With this, the authors argue that the relationship model can increase the spirit of villagers who work together, so that the village government and the community are intertwined with good governance, of course this existence raises the term good government as one of the efforts of community togetherness supported by various elements of society, communities, organizations as a form of jointly building villages in collaboration.